Fiscal Decentralization and Government Size: Evidence from a Panel of European Countries - Makreshanska mladenovska, Suzana; Petrevski, Goran (Instituto de Estudios Fiscales, 2019)
This paper provides empirical evidence on the association between fiscal decentralisation and govern-ment size on a sample of 28 European countries during 1990-2016. The main findings from our study are as follows: first, expenditure decentralisation is associated with smaller government size; second, revenue decentralisation has negative effect on government size only in the sub-sample of Central and Eastern European countries; third, we cannot provide empirical support to the common-pool hypoth-esis, implying that it is expenditure decentralisation that matters for the size of general government notwithstanding how sub-national governments finance their expenditure.
Keywords: Fiscal decentralisation, government size, Leviathan hypothesis, common-pool hypothesis, GMM